Marketing Plan for MSMEs to Improve the Performance of MSME Businesses: A Literature Review - Muhammad Endang Asmara; Zenni Riana (Universitas KH. Abdul Chalim Mojokerto, 2026)
Micro, Small, and Medium Enterprises operate in increasingly volatile and digitally driven markets where informal marketing practices often limit strategic growth. Although marketing planning has long been acknowledged as a critical managerial function, fragmented empirical findings and the absence of integrative synthesis leave its role in enhancing small enterprise performance conceptually underdeveloped. This study addresses this gap by conducting a systematic literature review of recent Scopusindexed publications to critically examine the relationship between marketing planning and business performance in small enterprises. Following a structured review protocol, selected studies were evaluated and synthesized thematically to identify dominant dimensions, mechanisms, and performance implications. The findings reveal that structured marketing planning—anchored in market analysis, segmentation, strategic positioning, and performance monitoring consistently strengthens both financial and nonfinancial outcomes. Moreover, integration with digital capabilities and market orientation amplifies its performance effects. The review advances the literature by consolidating dispersed insights into a coherent conceptual understanding of marketing planning as a strategic capability rather than a procedural activity. Practically, it underscores the necessity for small enterprises to institutionalize systematic marketing planning to achieve sustainable competitiveness in dynamic environments